CHLOROPHYLL CONTENT AND ITS RELATION TO PRODUCTIVITY OF CROPS AND WEEDS IN A TROPICAL AGROECOSYSTEM AT GUJAR LAKE MARGIN, INDIA - Singh, Mayank; Singh, Mahendra Pratap (Ecoprint: An International Journal of Ecology, 2016)
The paper deals with evaluation of magnitude of changes in chlorophyll concentration, chlorophyll density and relationship of chlorophyll density with net primary productivity of mixed winter crop (wheat and mustard) community at Gujar lake margin in the district Jaunpur (U.P.). The chlorophyll concentration of each component of crops, dominant weed Cynodon dactylon (Linn.) Pers. and ‘other weeds’ have shown increasing trend in the beginning and reached their peak values at the same time (75-90 days). Thereafter, chlorophyll concentration have declined sharply. Maximum chlorophyll density value of total crop (wheat and mustard) was 2015.77 mg m-2 and for total weeds was 810.08 mg m-2, both at the age of 90 days of crop. There was a significant positive correlation between productivity and chlorophyll density of total crop (r = 0.903, p = 0.002) and total weeds (r = 0.580, p = 0.131). ECOPRINT 23: 39-44, 2016